Pequenas e médias empresas e disclosure obrigatório : efeitos da adoção do IFRS, auditoria e endividamento - Guanandy, Francisca Nossa (2016)
This study aims to verify the effects of the IFRS adoption, external auditing and leverage on the accounting disclosure level of small and medium-sized enterprises. In order to evaluate the level of the mandatory accounting disclosure, this study analyzes the quantity of information disclosed by SMEs on their financial statements reported in “Diário Oficial” of five Brazilian states: Distrito Federal, Espírito Santo, Minas Gerais, Mato Grosso and São Paulo. To evaluate the level of mandatory accounting disclosure, this study considers the number of notes, the number of published financial statements and the number of accounts in their balance sheets. For this reason, this research uses the Regression method with Count Data. The results indicate that SMEs that reported in their notes that they apply as accounting standard the IFRS (Full or for SMEs), that contracted external audit services, especially of Big Four firms and that had high leverage, have a tendency to disclose a larger number of notes. In addition, SMEs that have stated that they are applying the IFRS for SMEs and were audited by Big Four have indicated a tendency to reduce the number of accounts in their balance sheets, which does not mean that the level of accounting disclosure in these companies is compromised, they also tend to disclose more notes and are therefore more transparent in this way, reducing the number of equity accounts and expanding the information contained therein.